2007
DOI: 10.1021/jp066714z
|View full text |Cite
|
Sign up to set email alerts
|

Ge−O Coordination in Cesium Germanate Glasses

Abstract: Neutron diffraction data with high real-space resolution are reported for an extensive series of cesium germanate glasses with 2, 5, 10, 15, 18, 21, 25, and 30 mol % Cs(2)O, and also for pure GeO(2) in its vitreous, quartz, and rutile forms. The results for pure GeO(2) show that neutron diffraction can clearly identify an increase in the Ge-O coordination number above the tetrahedral value of four. The results for cesium germanate glasses give strong evidence that the Ge-O coordination number rises to a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
118
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(132 citation statements)
references
References 82 publications
13
118
1
Order By: Relevance
“…Many spectroscopic and scattering studies of alkali germanate glasses have been reported, as reviewed recently [3,[5][6][7]. The overall pattern outlined above is generally supported, for example, by Raman scattering [8,9] and by X-ray and neutron scattering [10], including a recent, detailed study of cesium germanates [7].…”
Section: Introductionmentioning
confidence: 87%
“…Many spectroscopic and scattering studies of alkali germanate glasses have been reported, as reviewed recently [3,[5][6][7]. The overall pattern outlined above is generally supported, for example, by Raman scattering [8,9] and by X-ray and neutron scattering [10], including a recent, detailed study of cesium germanates [7].…”
Section: Introductionmentioning
confidence: 87%
“…1. The density of caesium germanate glasses as a function of composition [3,28]. The line is a guide to the eye.…”
Section: The Model For Borate Glassesmentioning
confidence: 99%
“…We have recently used pulsed neutron diffraction to measure the coordination number, n GeO , for a large number of caesium germanate glasses, covering a wide range in composition [28], and these results are shown as closed circles with error bars in Fig. 5.…”
Section: Application Of the Modelmentioning
confidence: 99%
“…Recent O K-edge XANES studies of alkali germanate glasses indicate that the coordination of Ge does indeed increase with the addition of alkalis [11][12][13][14][15][16][17][18]. Oxygen Kedge XANES has proven to be a very sensitive probe to determine the coordination of the metal to which the oxygen is bound [11,19].…”
Section: Introductionmentioning
confidence: 99%